THE VOLUME OF PRODUCTION IN UZBEKISTAN IS INCREASING (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Our daily life cannot be imagined without cars. The reason is that cars are a convenient means of transportation that makes our distance close and our burden light.